2013
DOI: 10.1103/physrevlett.111.066601
|View full text |Cite
|
Sign up to set email alerts
|

Multifractality at Anderson Transitions with Coulomb Interaction

Abstract: We explore mesoscopic fluctuations and correlations of the local density of states (LDOS) near localization transition in a disordered interacting electronic system. It is shown that the LDOS multifractality survives in the presence of the Coulomb interaction. We calculate the spectrum of multifractal dimensions in 2+ϵ spatial dimensions and show that it differs from that in the absence of interaction. The multifractal character of fluctuations and correlations of the LDOS can be studied experimentally by scan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 48 publications
(50 reference statements)
10
69
0
Order By: Relevance
“…Recently, this conclusion was supported by numerical analysis in the framework of the density functional theory [30], by the Hartree-Fock simulation of the problem [31], and by the authors within the nonlinear sigma model analysis in d = 2 + ǫ dimension in the case of broken time reversal and spin rotational symmetries [32].…”
Section: Introductionmentioning
confidence: 85%
“…Recently, this conclusion was supported by numerical analysis in the framework of the density functional theory [30], by the Hartree-Fock simulation of the problem [31], and by the authors within the nonlinear sigma model analysis in d = 2 + ǫ dimension in the case of broken time reversal and spin rotational symmetries [32].…”
Section: Introductionmentioning
confidence: 85%
“…This method has previously been successfully applied to the Anderson transition 12,13 . In addition, two recent papers 25,26 have shown that multi-fractality survives in the presence of the Coulomb interaction.…”
Section: Multi-fractal Finite Size Scaling Analysismentioning
confidence: 99%
“…Attempts to address this question have been performed in numerical analysis of disordered electrons with Coulomb interaction in the framework of functional density theory [28,29] and by numerical implementation of the Hartree-Fock scheme [30]. Recently, the detailed theory of mesoscopic fluctuations of the local density of states has been developed by the present authors within nonlinear sigma model treatment of disordered interacting electrons in d = 2 + dimensions [31][32][33]. It was demonstrated that moments of the local density of states at Mott-Anderson transitions behave generically similar to Eq.…”
Section: Pacsmentioning
confidence: 99%
“…In Refs. [31] it was shown that the q-th moment of the local density of states at E = T = 0 obeys the following scaling law:…”
Section: Pacsmentioning
confidence: 99%